Students acceptance on online learning - Choa, Pei Yee; Ahmad, Rosnani; Yahaya, Khairul Husna; Mohd Fauzi, Naajihatul Athirah; Yunos, Mohamad Yusri Shafiq; Abidin, Rahimi (2017)
Learning Management System (LMS) has been implemented in Universiti Utara Malaysia (UUM) since year 2000.LMS is one of the information technology tools that provide avenues for communication and knowledge sharing among lecturers and students.Due to its importance, the study meant to investigate the level of students’ acceptance towards online learning and its impact on their learning performance.Referring to the study, this article reflects critical outcomes in view of the impact on the students’ learning performance.There are 100 students from second, third and fourth year of Bachelor of Operation Management, from School of Technology Management and Logistics, Universiti Utara Malaysia (UUM) which has access of using Online Learning have been selected to participate.The framework of this study is based on Theory of Reasoned Action (TRA). This article shows that there is a significant and strong positive correlation between level of students' acceptance towards online learning and its impact on their learning performance. Equally important, this research is also expected to provide full suggestions on maximizing the benefits of Online Learning.